Financial Model Of Viability Gap Fund : Case Study on Palembang - Indralaya Toll Road Project - Eko Nur Surachman, Hadi Setiawan, (Badan kebijakan Fiskal, 2015)
Inadequate supply of infrastructure is number five of the most problematic factors for doing business in Indonesia. Therefore Government of Indonesia (GoI) continues to accelerate the development of infrastructure either in terms of financing, incentives, and especially through Public Private Partnership (PPP) scheme. One of the breakthroughs made by the government in the PPP scheme is by providing support in the form of cash funds for the construction cost of the project also called Viability Gap Fund (VGF), in order to make a project that was previously financially unviable to become financially viable. This study aims to describe about the possibility of VGF in accelerating infrastructure development through PPP scheme, as well as conduct a financial model to calculate whether VGF really can make a project financially viable with a case study on the Palembang - Indralaya Toll Road Project. Methodology used in this study is quantitative method with the financial analysis. IRR and NPV are used as main financial parameters to determine financial viability of the project. The research shows that VGF will make Palembang-Indralaya Toll Road Project become financially viable.